Comparison of populations of Melanagromyza sojae and Liriomyza sativae associated with Mung bean Vigna radiata (Linn.) Wilczek grown in Biratnagar, eastern Nepal - Thapa, Moon (Nepalese Journal of Biosciences, 2013)
DOI: http://dx.doi.org/10.3126/njbs.v2i0.7504 Nepalese Journal of Biosciences 2 : 154-155 (2012)